Sociological study of Ghanachakkar (TUTA Journal, 2024)
Sanjeev Upreti’s novel Ghanachakkar manifests different problems observed by a professor. In the history of Nepal innumerable murders, crimes and offenses have been but the truth behind them has not been revealed. Many crimes are committed to hide one crime. This is “Ghanachakkar”. As we have to forget the causes and impact of those murders or massacre, the author shows truth can come out if we move from place to place in the guise of a beggar or an investigator. The protagonist moves from place to place hiding his identity, then he gets some partial truth of those mysterious events. Novels can be useful to observe Sociology of Literature.